Oman: Partisan Non-Intervention - Barrett, Roby Carol; Sherwood, Leah (E-International Relations, 2024)
While Oman often adopts non-interventionist positions, it is an oversimplification to call it a neutral state.
Keywords: Politique étrangère – Oman – 2020-....

Oman, 'Assertive Diplomacy' and the Gaza Crisis - Worrall, James (2024)
With the Israel–Gaza conflict threatening to escalate tensions across the Middle East, Omani officials are stepping up their rhetoric in favour of peace, capitalising on their country’s reputation as a regional interlocutor.
Keywords: Politique étrangère – Oman – 2020-....

Oman: Navigating Peace Amidst Turmoil - Liberti, Sofia (Taylor university, 2023)
This paper provides insight on the ways in which the country of Oman could be best equipped to foster peace in the Middle East based on their history and unique theological approach to Islam. It uses Yemen as a case study.
Keywords: Politique étrangère – Oman – 2020-....

Oman toujours au cœur des recompositions régionales - Sorant, Marion (2023)
Marion Sorant, membre associée FMES de l’Observatoire stratégique de la Méditerranée etdu Moyen-Orient (OS2MO)
Keywords: Politique étrangère – Oman – 2020-....

Oman, médiateur du Golfe ? Caractéristiques d’une diplomatie singulière - Clément, Justine (Les clés du Moyen-Orient, 2023)
Keywords: Politique étrangère – Oman – 2020-....

Oman, discret artisan de la détente au Moyen-Orient (Le Monde.fr, 2023)
Le sultanat, qui a la confiance aussi bien des Etats-Unis et de l’Arabie saoudite que de l’Iran, mène une active diplomatie de médiation dans la région.
Keywords: Politique étrangère – Oman – 2020-....

Pourquoi le sultanat d’Oman a-t-il joué les intermédiaires entre la Belgique et l’Iran ? - Rotili, Lavinia (RTBF, 2023)
Après la libération de l’humanitaire belge Olivier Vandecasteele, trois autres otages européens ont été libérés par...
Keywords: Politique étrangère – Oman – 2020-....

Una politica estera da mediatore: coesistenza pacifica e non-intervento nell’Oman contemporaneo - Roggero, Caterina (2021)
Università Milano-Bicocca
Keywords: Politique étrangère – Oman – 2020-....